The Spatial Distribution of Pontoscolex corethrurus and Haemadipsa zeylanica in UiTM Negeri Sembilan Reserve Forest - Amir, Nurul Nurfatehah; Mohd Shariff, Syazuani (Journal of Sustainable Natural Resources, 2024)
Annelida, commonly found in terrestrial, freshwater, and marine environments, exhibits notable species diversity and ecological abundance. However, limited research has been conducted on Annelida in the UiTM Negeri Sembilan Forest Reserve, leading to a gap in understanding their ecological roles. This study aims to identify Annelida species and assess their diversity across four designated sites within the forest reserve. Sampling was carried out over four weeks using quadrats and hand-sorting techniques, with soil types classified through the Jar Test Method. A total of 77 Annelida specimens were collected: Site 1 (N = 14), Site 2 (N = 30), Site 3 (N = 11), and Site 4 (N = 22). Morphological identification revealed two species: Pontoscolex corethrurus (N = 70) and Haemadipsa zeylanica (N = 7). Species richness (R) was calculated at 0.23, with a diversity index (H) of 0.305 and evenness (E) of 0.44, indicating relatively low diversity. These findings contribute to the understanding and conservation of Annelida habitats in the forest reserve, highlighting the need for further research to explore the species diversity in greater depth.